Niat Beli Ulang Melalui Keputusan Pembelian pada Perusahaan Freight Forwarding - Hidayaatullah, Mukhlis; Tampubolon, Manahan; Simarmata, Juliater; Soekirman, Atong; Fachrial, Peppy (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2023)
Customers’ dissapointment of unsatisfactorily previous service make them reluctant to re-use the same service in the future. The purpose of the study is to determine and analyze the direct and indirect effect of service quality and corporate image on repurchase intention at shipping service company of PT DHL Global Forwarding Indonesia through purchasing decision. In this study, the random sampling technique using Slovin was used and resulted in a total sample of 135 customers. The analysis tool used SmartPLS application. The result of the study shows that purchasing decision has a positive direct effect on repurchase intention with a positive and significant relationship. The other hypothesis resulted that there is an indirect effect between service quality and corporate image on repurchase intention through purchasing decision, with a positive but not significant relationship. While, corporate image also has an indirect effect on repurchase intention through purchase decision with a positive and significant relationship. However, both service quality and corporate image have no direct effect on repurchase intention, with a positive but not significant relationship.